A study of nutritional anaemia among husm pregnant women and its corretation with the hematological parameters - Suhair Abbas, Ahmed Al- Salih (Pusat Pengajian Sains Perubatan, 2013)
Nutritional anaemia in pregnancy continues to be a common clinical problem in many developing countries and significantly contributes to maternal mortality and to both maternal and fetal morbidity. The objectives of this study were to determine the prevalence of anaemia and nutritional anaemia among pregnant women at HUSM and to look for correlation between haematological parameters and serum ferritin, serum folate, red cell folate and vitamin 812. A cross sectional study of pregnant women attending antenatal clinic at HUSM was conducted in year 2005. A systematic random sampling method was applied and 278 patients were recruited. Full blood count, serum ferritin, serum folate, red cell folate and vitamin B12 levels were determined by automated haematology analyzer Sysmex KX 21N and Access Immunoassay System respectively and results were analysed by SPSS version 12. The means (SDs) of age, period of amenorrhoea, and gravida were 31.1 (5.9) years, 20.7 (7.7) weeks and 3 (3) respectively. Sixty five percent (65%) of the study population were in the second trimester and 62.2 %were multigravida. Thirty seven percent (37%) were not on any haematinics while 11.9% were taking only one type of haematinics. The mean (SD) of hemoglobin level was 11.3 g/dL(l.l). The prevalence of anaemia (defined by haemoglobin less than 11.0g/dl) was 37.0 % . The means (SDs) for serum ferritin, serum folate, vitamin 812 and red cell folate were 17.7 ~Jg/L (30.4), 22.9 nmoi/L (13.0), 284.6 pmoi/L (135.7) and 951.6 nmoi/L (441.5) respectively. Serum ferritin less than 12.0 ~Jg/L were recorded in 34.7% of patients and 47.6% had serum ferritin between 12.0 11g/L and 50.0 11g /L. Among those with serum ferritin less than 12.0 llg/1, half of them (50.0%) had iron deficiency anaemia whereas the other 50.0% were in the state of iron deficiency. Four patients (1.5 %) had folate deficiency defined by red cell folate less than 372 nmol/1. Three patients (1.2%) probably had vitamin 812 deficiency as defined by vitamin 812 less than 107.0 pmol/1. Gestational age and folate intake were found to be significantly associated with anaemia in pregnancy. Significant positive correlations noted between haemogobin levels and other red cell parameters. Mean cell haemoglobin showed a significant correlation as a predictor for red cell folate, however other haematologkal parameters were not significantly correlated as a predictor for serum ferritin, folate or vitamin 812. In conclusion, the prevalence of anaemia among pregnant women at HUSM is high with iron deficiency being the commonest nutritional deficiency. In addition, it was shown that the assessment of iron, folate or vitamin 8l2 status cannot be predicted by haemoglobin levels or other red cell parameters. It is therefore recommended to perform full blood count and serum ferritin together in pregnant women in centres with facilities, whereas folate and vitamin 812 level are recommended for pregnant mother with clinical suspicion and risk factors .